Melonworm, Diaphania hyalinata Linnaeus (Insecta: Lepidoptera: Pyralidae) - John L. Capinera (EDIS)
Melonworm, Diaphania hyalinata Linnaeus, occurs throughout most of Central and South America and the Caribbean. The United States is the northern limit of its permanent range, and wintertime occurrence generally is limited to south Florida and perhaps south Texas. Melonworm disperses northward annually. Its distribution during the summer months is principally the southeastern states, though occasionally it disperses north to New England and the Great Lakes region. This document is EENY-163, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000.